Theoretical background of innovation inservices in small and medium-sized enterprises: Literature mapping - Saymon Ricardo de Oliveira Sousa; Wesley Vieira da Silva; Claudimar Pereira da Veiga; Roselaine Ruviaro Zanini (Journal of Innovation and Entrepreneurship, 2020)
The aim of this study was to map the innovation of services in small and medium-sized enterprises, as reported on the Web of Science and SCOPUS databases, using a structured review, involving 121 papers published between 1946 and 2019. There has been an increase in the number of studies in recent years, covering 23 countries on six continents, with the UK representing 48.78% of the studies. Patterns in the use of methods applied in research were identified, as well as a conceptual structure of the field. The main areas of science were finance, marketing, energy, and green engineering. The study makes an original contribution to the literature, highlighting the interest in the expansion of knowledge among the academic community, in addition to enabling a deeper analysis of the relation between the evaluated constructs.
Keywords: 650; Innovation in services; Small and medium-sized enterprises; Literature mapping; Systematic literature review